Tree Cavities as Microhabitats Shared by Multiple Taxa: Understanding the Coexistence of an Arboreal Marsupial with Other Cavity-Dwelling Vertebrates in Southern Temperate Forests - Vergara-Egert, P; Quiroz-Espinoza, M; Fierro-Tapia, C; Moreira-Arce, D; Alaniz-Baeza, A; Carvajal-Leon, M; Zuñiga-Alvarez, A; Hidalgo-Corrotea, C (John Wiley and Sons Inc, 2025)
[No abstract available]